مظاهر التعصب الغربي ضد الإسلام و أثره على الحوار الاسلامي المسيحي بعد أحداث 11 سبتمبر 2001 - عبداللاوي, عبدالحليم (University of eloued جامعة الوادي, 2018)
"تحاول هذه الدراسة تحليل تهمة الإرهاب والتطرف، التي أصبحت حكراً على الإسلام، من منطلق تطوره في السياق الفكري الغربي، أين سنركز على دراسة العلاقة المتوترة للغاية بين الإسلام والغرب حديثاً في أعقاب أحداث 11 سبتمبر.تحددت الإشكالية بالصيغة التالية: ماهي مظاهر التعصب الغربي ضد الإسلام وتأثيرها السلبي على الحوار بين الإسلام والمسيحية؟ بعد أحداث 11 سبتمبر2001. وهدفت الدراسة إلى تسليط الضوء على أهم مظاهر التعصب على مسار الحوار بين الإسلام والمسيحية، وكيف هو واقع ومستقبل المسلمين في الغرب بعد هجمات أحدث 11 سبتمبر" At all stages the relations between Islam and the Christian world were dominated by stereotypes pictures that were specific to one another also , the Historical events have played a clear role in developing the intellectual perception of the parties when the Analysis of the West's relationship with Islam may require a return to history to break the stages of the cognitive development of these images to each other in order to better understand the renewed conflict between the parties. This study attempted to analyze the concept of terrorism and extremism which has become the monopoly of Islam, for studying the large of relationship between Islam and the West , recently in the wake of the events of 11 September. The problem was defined as follows: What are the manifestations of Western intolerance against Islam and its negative impact on dialogue between Islam and Christianity? After the events of 11 September 2001.
Keywords: الإسلام، الغرب، الإرهاب، الحوار، التعصب، التطرف.; Islam, West, Terrorism, Dialogue, Intolerance, Extremism.